Increasing Cardiovascular Endurance (Vo2max) Through High Intensity Interval Training (Hiit) Methode In Athletes - Hardi, Alif Aryadi; Rijaluddin, Khalid; Dos Santos, Maria Herlinda; Kausar, Audri; Azwin, Muh. (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2025)
This study aims to determine the effect and effectiveness of the high-intensity interval training (HIIT) method on increasing cardiovascular endurance (VO2max) in athletes. This study used a quasi-experimental design. One group became the experimental group, and the other the control group. The research design used a nonequivalent control group design. The population in this study were all badminton athletes of the PB Kobar club, with a total of 24 people. Because the population size was less than 100, the sampling technique used a total sampling technique. So the sample of this study was 24 people. 12 people in the experimental group and 12 people in the control group. Each group (experimental and control) was given treatment with a frequency of 12 times, which was carried out 3 times a week. This study used a beep test as a research instrument. Data analysis used the Shapiro-Wilk test for data normality testing and Levene's test for data homogeneity testing. For hypothesis testing, the T-test (paired sample t-test) was used. The N-Gain score test was used to measure the effectiveness of the treatment using SPSS 27 software. The results showed that: (1) There was a significant effect on the cardiovascular endurance of athletes participating in high-intensity interval training (P<0.05). (2) There was a significant effect on the cardiovascular endurance of athletes participating in conventional training (P<0.05). (3) High-intensity interval training was more effective in increasing athletes' cardiovascular endurance with a percentage value of 59.67% compared to conventional training with a percentage value of 24.18%. It can be concluded that the application of the High-Intensity Interval Training (HIIT) method is more effective in increasing cardiovascular endurance compared to conventional training